Preparation method of MOF modified lithium manganese iron phosphate and material thereof

CN122977339APending Publication Date: 2026-10-27JIANGXI GANFENG BATTERY TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611083666.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0023]本发明方法制备改性后的磷酸锰铁锂复合材料LFMP/C@MOF,综合性能优异,具备导电性佳、锰溶出率低、电化学活性高、压实密度高四大核心优势。而且颗粒中MOF多孔结构与双层碳包覆夹层结构,构建双重导电网络,有效优化导电通路、降低界面阻抗,大幅提升电子传导与锂离子迁移效率,改善材料倍率性能,减小充放电极化现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977339A_ABST
    Figure CN122977339A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of MOF modified manganese iron lithium phosphate, comprising the following steps: S1, mixing a phosphorus salt solution, a reducing agent and a manganese iron metal solution; S2, uniformly mixing di-lithium hydrogen phosphate, a first carbon source and a precursor (Fe 0.5 Mn 0.5 )2PO4 in water, stirring for a period of time to obtain mixed slurry, and then performing sand grinding, spray drying and first sintering treatment on the mixed slurry to obtain manganese iron lithium phosphate particles LFMP / C coated with a carbon layer; S3, mixing the manganese iron lithium phosphate particles LFMP / C with an organic solvent, a metal compound and an organic ligand, and then putting the mixture into a polytetrafluoroethylene-lined stainless steel reaction kettle; S4, uniformly mixing the LFMP / C@MOF and a second carbon source to obtain mixed slurry, and then performing filtering, drying, second sintering and crushing on the sintered material to obtain modified manganese iron lithium phosphate particles LFMP / C@MOF / C. The modified manganese iron lithium phosphate composite material prepared by the method has four core advantages of good electrical conductivity, low manganese dissolution rate, high electrochemical activity and high tap density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery cathode material preparation, specifically relating to the preparation method and materials of MOF-modified lithium manganese iron phosphate. Background Technology

[0002] Lithium-ion batteries dominate the consumer electronics, energy storage, and new energy vehicle sectors due to their advantages such as long cycle life, high energy density, and environmental friendliness. While LiFePO4 cathodes offer stable structure and are safe and environmentally friendly, their low energy density and slow charging speed limit their large-scale application in the transportation sector. LiMnPO4, with a higher operating voltage but comparable theoretical capacity to LiFePO4, boasts a 21% increase in theoretical energy density. It also shares the olivine structure, offers excellent safety, is cobalt- and nickel-free, and has lower costs, making it a highly promising next-generation cathode. However, LiMnPO4 has a hexagonal close-packed structure, with FeO6 and MnO6 located on octahedra and interconnected through PO4 tetrahedra. The absence of a continuous FeO6 (MnO6) edge-sharing octahedral network results in poor conductivity. Furthermore, the PO4 tetrahedra located between FeO6 (MnO6) octahedra block lithium-ion diffusion channels, restricting their movement to one-dimensional channels and leading to a low lithium-ion diffusion rate and poor rate performance. These shortcomings prevent lithium manganese iron phosphate materials from fully realizing their electrochemical performance, thus limiting their further large-scale application. Therefore, it is essential to develop a modified lithium manganese iron phosphate material with excellent conductivity and high safety to address the current prominent problems and accelerate the application of lithium manganese iron phosphate.

[0003] MOF materials combine structural designability with excellent stability, and can achieve good conductivity through proper construction. They form an ordered porous framework composed of metal nodes and organic ligands. By using high-charge metals and rigid aromatic carboxylic acid ligands, stable structures that are resistant to acids and alkalis, high temperatures, and are not easily collapsed can be constructed, maintaining pore integrity even in complex environments. These materials possess both stable framework support and efficient charge transport channels, showing outstanding application potential in electrocatalysis, energy storage, gas separation, and sensing. Therefore, it is crucial to modify MOF materials by mixing them with lithium manganese iron phosphate to improve their conductivity, safety, and cycle performance. Summary of the Invention

[0004] To improve the conductivity, safety, and cycle life of lithium manganese iron phosphate in existing technologies, this invention provides a method for preparing MOF-modified lithium manganese iron phosphate, comprising the following steps:

[0005] S1: Mix the phosphate salt solution, reducing agent, and manganese-iron metal solution, stir until homogeneous, then add a pH adjusting agent to adjust the pH of the mixed solution to 8-9.5. After stirring for 3-4 hours, filter and wash to obtain the precursor (Fe).0.5 Mn 0.5 )2PO4; wherein the molar ratio of the phosphate salt, manganese iron metal, and reducing agent is 1:0.5~1.5:0.01~0.17;

[0006] S2: Lithium hydrogen phosphate, the first carbon source, and the precursor (Fe) are added. 0.5 Mn 0.5 )2PO4 is mixed evenly in water and stirred for a period of time to obtain a mixed slurry. The mixed slurry is then sand-milled, spray-dried, and subjected to a first sintering treatment to obtain lithium manganese iron phosphate particles LFMP / C coated with a carbon layer.

[0007] S3: The lithium manganese iron phosphate particles LFMP / C are mixed with organic solvent, metal compound, and organic ligand and then placed into a stainless steel reactor lined with polytetrafluoroethylene. The mixture is heated at 120℃~180℃ for 12h~24h, followed by filtration and washing to obtain LFMP / C@MOF. The mass ratio of LFMP / C, metal compound, and organic ligand is 100:0.6~2.5:2.5~5.

[0008] S4: Mix the LFMP / C@MOF and the second carbon source evenly to obtain a mixed slurry, and then filter, dry, and sinter the slurry for a second time. After crushing the sintered material, the modified lithium manganese iron phosphate particles LFMP / C@MOF / C are obtained.

[0009] Further, the phosphate salt solution in step S1 is one or more of sodium phosphate, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.

[0010] Further, the reducing agent in step S1 is one or more of sodium borohydride, ascorbic acid, or oxalic acid.

[0011] Furthermore, the manganese-iron metal solution includes a manganese source and an iron source. The manganese source in step S1 is one or more of manganese sulfate monohydrate, manganese chloride tetrahydrate, or manganese acetate tetrahydrate; the iron source is one or more of ferrous oxalate, ferrous sulfate heptahydrate, or ferrous chloride tetrahydrate.

[0012] Furthermore, the pH adjusting agent is one or more of ammonia, ammonium carbonate, potassium hydroxide, and sodium hydroxide.

[0013] Furthermore, the organic solvent in step S3 is one or more of DMF, DMA, NMP, methanol, ethanol, ethylene glycol, and glycerol.

[0014] Further, the organic ligands are one or more of the following: pyromellitic acid, terephthalic acid, aminoterephthalic acid, biphenyl terephthalic acid, fumaric acid; imidazoles such as 2-methylimidazolium and benzimidazole; nitrogen-containing heterocyclic compounds such as 4,4'-bipyridine; triphosphates and porphyrins.

[0015] Furthermore, the soluble metal compound is one or more of the following: titanium oxysulfate, zinc nitrate, copper nitrate, ferric chloride, chromium nitrate, aluminum nitrate, cobalt nitrate, nickel nitrate, and magnesium nitrate.

[0016] Furthermore, in step S2, the inlet air temperature of the spray drying is 220~250℃, and the outlet air temperature is 90~105℃; the sintering temperature of the first sintering treatment is 600~800℃, and the sintering time is 2~12h.

[0017] Furthermore, in step S1, the concentration of phosphate salt is 0.8~1.5 mol / L, the concentration of reducing agent is 0.1~1% by mass, the concentration of iron-manganese metal solution is 0.8~1.5 mol / L, and the conductivity of the filter cake after washing is 200~500 μS / cm.

[0018] Furthermore, the first carbon source is one or more of glucose, sucrose, PEG2000~6000, starch, chitosan, lignin, and polyacrylol.

[0019] Furthermore, the second carbon source is one or more soluble carbon sources such as glucose and sucrose.

[0020] Furthermore, the drying temperature in step S4 is set to 60℃~95℃, and the second sintering temperature is set to 650℃~850℃.

[0021] Furthermore, the grinding particle size in step S2 is 0.2~0.45μm, the inlet air temperature of spray drying is 220~250℃, the outlet air temperature is 90~105℃, the sintering temperature is 600~800℃, the maximum temperature holding time is 2~12h, and the particle size of the obtained sample after crushing is 0.85~2.7μm.

[0022] On the other hand, the present invention provides a lithium manganese iron phosphate cathode material, comprising a lithium manganese iron phosphate core, and an outer layer sequentially coated with a carbon layer, a MOF layer, and another carbon layer.

[0023] The method of this invention prepares a modified lithium manganese iron phosphate composite material LFMP / C@MOF, which exhibits excellent comprehensive performance, possessing four core advantages: good conductivity, low manganese leaching rate, high electrochemical activity, and high compaction density. Furthermore, the porous MOF structure and the double-layer carbon-coated sandwich structure within the particles construct a dual conductive network, effectively optimizing the conductive pathway, reducing interfacial impedance, significantly improving electron conduction and lithium-ion migration efficiency, enhancing the material's rate performance, and reducing charge-discharge polarization. Attached Figure Description

[0024] Figure 1 This is a flowchart of the preparation method of MOF-modified lithium manganese iron phosphate according to the present invention and a schematic diagram of the resulting material structure;

[0025] Figure 2 This is a SEM image of the modified lithium manganese iron phosphate particles prepared in Example 1 of the present invention;

[0026] Figure 3 SEM image of lithium manganese iron phosphate particles prepared in Comparative Example 1 of this invention.

[0027] Figure 4 This is a SEM image of the lithium iron phosphate particles prepared in Comparative Example 2 of this invention. Detailed Implementation

[0028] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0029] Example 1

[0030] like Figure 1 As shown, this embodiment modifies lithium manganese iron phosphate according to the following steps:

[0031] Step S1: Add 1 L of 1 mol / L ammonium dihydrogen phosphate solution to a 2 L manganese-iron metal solution containing 10 g ascorbic acid. The manganese-iron metal solution contains Fe... 2+ Concentration of 0.5 mol / L and Mn 2+ The green solid suspension was prepared by filtration and washing in a 0.5 mol / L metal mixed solution, with the pH adjusted to 8.50 using ammonia. The resulting suspension was then used to obtain the precursor (Fe). 0.5 Mn 0.5 )2PO4.

[0032] Step S2: The above precursor (Fe) 0.5 Mn 0.52PO4, 110g of lithium hydrogen phosphate, and 20g of glucose were added to 2000mL of pure water and mixed evenly to obtain a slurry. The slurry was then milled with a particle size D50 of 0.25μm. After milling, the slurry was spray-dried with an inlet air temperature of 230℃ and an outlet air temperature of 95℃. The spray-dried particles were then sintered for the first time at a temperature of 650℃ for 5 hours. Finally, the sintered particles were crushed to obtain modified lithium manganese iron phosphate particles with an outer carbon layer, namely LFMP / C.

[0033] Step S3: Place 100g of LFMP / C prepared in step S2, 500ml of LDMF, 1.56g of titanium oxysulfate, and 3.12% pyromellitic acid into a 1L stainless steel reactor lined with polytetrafluoroethylene. Heat at 150℃ and keep warm for 15h. Then filter and wash to obtain lithium manganese iron phosphate LFMP / C@MOF with a MOF layer coated on the outside of the carbon layer.

[0034] Step S4: Mix the gray-black LFMP / C@MOF solid prepared in step S3 with 50 ml of 20% glucose solution, dry the mixed solution at 80°C to constant weight, and sinter the dried particles at 700°C for 10 h; finally, crush the obtained product to obtain modified lithium manganese iron phosphate particles LFMP / C@MOF / C with a carbon layer coated on the outside of the MOF layer.

[0035] Example 1-1

[0036] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that phosphoric acid is used as the phosphate salt solution in step S1 of Example 1-1.

[0037] Examples 1-2

[0038] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that ammonium phosphate is used as the phosphate salt solution in step S1 of Example 1-2.

[0039] Examples 1-3

[0040] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that the phosphate salt solution in step S1 of Example 1-3 is ammonium hydrogen phosphate.

[0041] Examples 1-4

[0042] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that ammonium carbonate is used as the pH adjustment reagent in step S1 of Example 1-4.

[0043] Examples 1-5

[0044] The experimental scheme and steps in this implementation are the same as those in Example 1, except that the pH value is adjusted to 8.0 in step S1 of Example 1-5.

[0045] Examples 1-6

[0046] The experimental scheme and steps in this implementation are the same as those in Example 1, except that the pH value is adjusted to 9.0 in step S1 of Example 1-6.

[0047] Examples 1-7

[0048] The experimental scheme and steps in this implementation are the same as those in Example 1, except that the pH value is adjusted to 9.5 in step S1 of Example 1-7.

[0049] Example 2-1

[0050] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that the mass of lithium hydrogen phosphate in step S2 of Example 2-1 is 105g.

[0051] Example 2-2

[0052] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that the mass of lithium dihydrogen phosphate in step S2 of Example 2-2 is 115g.

[0053] Example 2-3

[0054] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the first carbon source in step S2 of Examples 2-3 is 20g of sucrose.

[0055] Examples 2-4

[0056] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the first carbon source in step S2 of Examples 2-4 is 20g of starch.

[0057] Examples 2-5

[0058] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the first carbon source in step S2 of Examples 2-5 is 10g of glucose and 10g of sucrose.

[0059] Examples 2-6

[0060] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the first carbon source in step S2 of Examples 2-6 is 10g of sucrose and 10g of starch.

[0061] Examples 2-7

[0062] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the first carbon source in step S2 of Examples 2-7 is 10g of glucose and 10g of starch.

[0063] Examples 2-8

[0064] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the sand grinding particle size in step S2 of Examples 2-8 is 0.2μm.

[0065] Examples 2-9

[0066] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the sand grinding particle size in step S2 of Examples 2-9 is 0.3 μm.

[0067] Example 3-1

[0068] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that the organic solvent used in step S3 of Example 3-1 is ethanol.

[0069] Example 3-2

[0070] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that the organic solvent used in step S3 of Example 3-2 is DMA.

[0071] Example 3-3

[0072] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that the organic solvent used in step S3 of Example 3-3 is NMP.

[0073] Examples 3-4

[0074] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the metal compound used in Examples 3-4 is nickel nitrate.

[0075] Examples 3-5

[0076] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that the metal compound used in Examples 3-5 is cobalt nitrate.

[0077] Examples 3-6

[0078] The experimental scheme and steps in this embodiment are the same as those in Example 1, except that the metal compound used in Examples 3-6 is magnesium nitrate.

[0079] Examples 3-7

[0080] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the organic ligand used in Examples 3-7 is terephthalic acid.

[0081] Examples 3-8

[0082] The experimental scheme and steps in this embodiment are the same as those in Example 1. The difference is that the organic ligand used in Examples 3-8 is biphenyl dicarboxylic acid.

[0083] Example 4-1

[0084] The experimental scheme and steps in this embodiment are the same as those in Embodiment 1, except that the second carbon source in step S4 of Embodiment 4-1 is sucrose.

[0085] Example 4-2

[0086] The experimental scheme and steps in this embodiment are the same as those in Embodiment 1, except that the drying temperature in step S4 of Embodiment 4-2 is set to 60°C.

[0087] Example 4-3

[0088] The experimental scheme and steps in this embodiment are the same as those in Embodiment 1. The difference is that the sintering temperature in step S4 of Embodiment 4-3 is 750℃ and the sintering time is 10h.

[0089] Example 4-4

[0090] The experimental scheme and steps in this embodiment are the same as those in Embodiment 1. The difference is that the sintering temperature in step S4 of Embodiment 4-4 is 780℃ and the sintering time is 10h.

[0091] Comparative Example 1

[0092] Step S1: Add 1 L of 1 mol / L ammonium dihydrogen phosphate solution to a 2 L manganese-iron metal solution containing 10 g ascorbic acid. The manganese-iron metal solution contains Fe... 2+ Concentration of 0.5 mol / L and Mn 2+ The green solid suspension was prepared by filtration and washing in a 0.5 mol / L metal mixed solution, with the pH adjusted to 8.50 using ammonia. The resulting suspension was then used to obtain the precursor (Fe). 0.5 Mn 0.5 )2PO4.

[0093] Step S2: The above precursor (Fe) 0.5 Mn 0.52PO4, 110g of lithium hydrogen phosphate, and 20g of glucose were added to 2000mL of pure water and mixed evenly to obtain a slurry. The slurry was then milled with a particle size D50 of 0.25μm. After milling, the slurry was spray-dried with an inlet air temperature of 230℃ and an outlet air temperature of 95℃. The spray-dried particles were then sintered for the first time at a temperature of 650℃ for 5 hours. Finally, the sintered particles were crushed to obtain modified lithium manganese iron phosphate particles with an outer carbon layer, namely LFMP / C.

[0094] Comparative Example 2

[0095] Step S1: Add 1 L of 1 mol / L ammonium dihydrogen phosphate solution to a 2 L manganese-iron metal solution containing 10 g ascorbic acid. The manganese-iron metal solution contains Fe... 2+ Concentration of 0.5 mol / L and Mn 2+ The green solid suspension was prepared by filtration and washing in a 0.5 mol / L metal mixed solution, with the pH adjusted to 8.50 using ammonia. The resulting suspension was then used to obtain the precursor (Fe). 0.5 Mn 0.5 )2PO4.

[0096] Step S2: The above precursor (Fe) 0.5 Mn 0.5 2PO4, 110g of lithium hydrogen phosphate, and 20g of glucose were added to 2000mL of pure water and mixed evenly to obtain a slurry. The slurry was then milled with a particle size D50 of 0.25μm. After milling, the slurry was spray-dried with an inlet air temperature of 230℃ and an outlet air temperature of 95℃. The spray-dried particles were then sintered for the first time at a temperature of 650℃ for 5 hours. Finally, the sintered particles were crushed to obtain modified lithium manganese iron phosphate particles with an outer carbon layer, namely LFMP / C.

[0097] Step S3: Place 100g of LFMP / C prepared in step S2, 500ml of LDMF, 1.56g of titanium oxysulfate, and 3.12% pyromellitic acid into a 1L stainless steel reactor lined with polytetrafluoroethylene. Heat at 150℃ and keep warm for 15h. Then filter and wash to obtain lithium manganese iron phosphate LFMP / C@MOF with a MOF layer coated on the outside of the carbon layer.

[0098] Powder performance testing;

[0099] The particle size, specific surface area, powder compaction density, and carbon content of the cathode particles formed in the above embodiments and comparative examples are tested. The test results of each embodiment and comparative example are shown in Table 1 below.

[0100] Battery performance test

[0101] The lithium manganese iron phosphate particles prepared by the above method were used as the positive electrode active material after airflow crushing. A slurry of positive electrode active material, SP (superconducting carbon black), and PVDF (polyvinylidene fluoride) in a mass ratio of 90:5:5 was homogenized and coated onto a 20μm thick aluminum foil. The slurry was then dried, rolled, die-cut, and punched into positive electrode sheets. The lithium sheet served as the negative electrode. A PE separator was used, and 80μL of electrolyte was added to assemble the cells into button batteries. The button batteries prepared above were tested using a blue electric current tester. The prepared button batteries were placed in a 25℃ incubator for charge and discharge tests within a voltage range of 2.0-4.2V. One cycle of 0.1C charge and discharge activation was performed, followed by discharge capacities under constant current and constant voltage charging and discharging at 0.1C, 0.5C, and 1C, as shown in Table 1.

[0102] Example 1 1.902 2.77 14.5145 10.210 0.0801 2.653 151.35 149.95 Example 1-1 1.796 2.69 14.7704 11.940 0.0798 2.595 151.50 146.81 Examples 1-2 1.707 2.61 11.4458 10.889 0.0803 2.610 152.91 148.19 Examples 1-3 1.791 2.49 10.7460 14.786 0.0796 2.587 152.14 147.46 Examples 1-4 1.710 2.31 11.4688 12.656 0.0805 2.616 154.73 150.00 Examples 1-5 1.813 2.22 11.8832 11.662 0.0806 2.518 155.29 150.55 Examples 1-6 1.889 2.09 12.1268 11.322 0.0795 2.485 153.67 149.00 Examples 1-7 1.698 2.12 11.8881 12.667 0.0799 2.597 153.85 149.15 Example 2-1 1.804 2.89 12.3246 11.603 0.0802 2.605 154.81 150.10 Example 2-2 1.795 2.86 12.6619 11.864 0.0798 2.493 154.54 149.85 Example 2-3 1.707 2.81 13.1526 11.627 0.0803 2.510 156.12 151.41 Examples 2-4 1.603 1.70 13.5271 11.413 0.0802 2.505 156.31 151.60 Examples 2-5 1.809 2.61 13.9698 19.055 0.0804 2.513 157.29 152.56 Examples 2-6 1.896 2.50 14.2714 18.323 0.0798 2.495 156.69 152.00 Examples 2-7 1.509 2.41 14.7887 19.748 0.0805 2.414 158.45 153.72 Examples 2-8 1.793 2.39 15.0396 20.767 0.0797 2.390 157.37 152.69 Examples 2-9 1.611 1.71 13.4945 20.504 0.0806 2.518 157.40 153.07 Example 3-1 1.605 2.63 13.8415 19.689 0.0802 2.508 157.27 152.96 Example 3-2 1.693 2.43 14.1432 10.538 0.0797 2.490 156.67 152.39 Example 3-3 1.809 2.41 14.6734 12.422 0.0804 2.513 158.59 154.27 Examples 3-4 1.805 2.31 15.0451 11.996 0.0802 2.508 158.78 154.46 Examples 3-5 1.703 2.20 15.4309 18.377 0.0802 2.405 159.12 154.81 Examples 3-6 1.898 2.10 15.7842 17.233 0.0799 2.398 159.14 154.85 Examples 3-7 1.705 2.11 16.2487 12.377 0.0802 2.407 160.28 155.97 Examples 3-8 1.603 3.11 15.9319 11.102 0.0802 2.505 158.32 154.01 Example 4-1 1.605 2.11 16.3490 21.424 0.0802 2.407 158.98 154.66 Example 4-2 1.712 2.92 16.8177 28.630 0.0806 2.417 160.12 155.79 Example 4-3 1.811 2.82 17.2032 21.489 0.0805 2.414 160.46 156.14 Example 4-4 0.910 1.72 19.7169 56.249 1.2639 2.346 152.17 142.77 Comparative Example 1 1.314 2.02 17.7553 40.698 0.1213 2.447 151.47 143.88 Comparative Example 2 1.813 2.22 11.8832 11.662 0.0806 2.518 155.29 150.55

[0103] The lithium manganese iron phosphate composite material prepared by this method exhibits excellent comprehensive performance, possessing four core advantages: good conductivity, low manganese dissolution rate, high electrochemical activity, and high compaction density. The product utilizes fine pretreatment through sand milling to optimize particle morphology, combined with a MOF porous structure and a double-layer carbon-coated sandwich structure to construct a dual conductive network. This effectively optimizes the conductive pathway, reduces interfacial impedance, significantly improves electron conduction and lithium-ion migration efficiency, enhances the material's rate performance, and reduces charge-discharge polarization. Simultaneously, relying on the co-precipitated regular lattice structure, combined with the physical protection of the dense MOF coating and the defect-sealing design of the composite coating layer, it effectively isolates electrolyte corrosion, inhibits manganese ion dissolution and interfacial side reactions, avoids negative electrode failure and positive electrode lattice collapse problems, and significantly improves battery cycle stability. Furthermore, process optimization achieves particle sphericity and uniformity, and the double-layer carbon coating enhances particle mechanical strength, effectively reducing particle agglomeration and breakage, narrowing particle packing gaps, overcoming the shortcomings of traditional materials in terms of compaction density, and significantly improving the utilization rate of active materials and the overall electrochemical performance of the battery.

[0104] This invention first coats lithium manganese iron phosphate with a layer of carbon, then crushes the resulting particles, controlling the particle size to be between 0.85 and 2.7 μm, and then coats them in situ with MOF (Metal-Oxide-Foil). Finally, a second carbon layer is coated on the outer layer of the MOF. This coating effectively inhibits particle fusion and adhesion during high-temperature secondary sintering, ensuring concentrated particle size distribution, high particle sphericity, and denser particle arrangement during electrode compaction. The double-coated lithium manganese iron phosphate exhibits excellent mechanical compressive strength. During the rolling preparation of electrodes, particle breakage and pulverization do not occur, avoiding the blockage of electrode pores by broken ultrafine particles, which would lead to a decrease in processing performance. Under high-compaction conditions, the particle structure can still be maintained, breaking through the technical bottleneck of low compaction density of traditional lithium manganese iron phosphate.

[0105] Furthermore, the MOF material grown in situ on the surface of lithium manganese iron phosphate particles in this invention has a multi-level porous structure. The electrolyte can fully wet the surface of the cathode particles, greatly increasing the effective reaction contact area of ​​the electrode / electrolyte and exposing more electrochemical active sites. Lithium ions do not need to diffuse long distances in the dense coating layer, but can quickly reach the surface of the active material through the MOF channels to participate in the redox reaction, significantly improving the lithium insertion and extraction kinetics performance, and improving the low-temperature discharge performance and rate performance.

[0106] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing MOF-modified lithium manganese iron phosphate, characterized in that, Includes the following steps: S1: Mix the phosphate salt solution, reducing agent, and manganese-iron metal solution, stir until homogeneous, then add a pH adjusting agent to adjust the pH of the mixed solution to 8-9.

5. After stirring for 3-4 hours, filter and wash to obtain the precursor (Fe). 0.5 Mn 0.5 )2PO4; wherein the molar ratio of the phosphate salt, manganese iron metal, and reducing agent is 1:0.5~1.5:0.01~0.17; S2: Lithium hydrogen phosphate, the first carbon source, and the precursor (Fe) are added. 0.5 Mn 0.5 )2PO4 is mixed evenly in water and stirred for a period of time to obtain a mixed slurry. The mixed slurry is then sand-milled, spray-dried, and subjected to a first sintering treatment to obtain lithium manganese iron phosphate particles LFMP / C coated with a carbon layer. S3: The lithium manganese iron phosphate particles LFMP / C are mixed with organic solvent, metal compound, and organic ligand and then placed into a stainless steel reactor lined with polytetrafluoroethylene. The mixture is heated at 120℃~180℃ for 12h~24h, followed by filtration and washing to obtain LFMP / C@MOF. The mass ratio of LFMP / C, metal compound, and organic ligand is 100:0.6~2.5:2.5~5. S4: Mix the LFMP / C@MOF and the second carbon source evenly to obtain a mixed slurry, and then filter, dry, and sinter the slurry for a second time. After crushing the sintered material, the modified lithium manganese iron phosphate particles LFMP / C@MOF / C are obtained.

2. The preparation method of MOF-modified lithium manganese iron phosphate according to claim 1, characterized in that, The phosphate solution in step S1 is one or more of sodium phosphate, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.

3. The method for preparing MOF-modified lithium manganese iron phosphate according to claim 1, characterized in that, The reducing agent in step S1 is one or more of sodium borohydride, ascorbic acid, or oxalic acid.

4. The method for preparing MOF-modified lithium manganese iron phosphate according to claim 1, characterized in that, The manganese-iron metal solution includes a manganese source and an iron source. The manganese source in step S1 is one or more of manganese sulfate monohydrate, manganese chloride tetrahydrate, or manganese acetate tetrahydrate; the iron source is one or more of ferrous oxalate, ferrous sulfate heptahydrate, or ferrous chloride tetrahydrate.

5. The method for preparing MOF-modified lithium manganese iron phosphate according to claim 1, characterized in that, The pH adjusting reagent is one or more of ammonia, ammonium carbonate, potassium hydroxide, and sodium hydroxide.

6. The method for preparing MOF-modified lithium manganese iron phosphate according to claim 1, characterized in that, The organic solvent in step S3 is one or more of DMF, DMA, NMP, methanol, ethanol, ethylene glycol, and glycerol.

7. The method for preparing MOF-modified lithium manganese iron phosphate according to claim 1, characterized in that, The organic ligands mentioned are pyromellitic acid, terephthalic acid, aminoterephthalic acid, biphenyl terephthalic acid, fumaric acid; imidazoles such as 2-methylimidazolium and benzimidazole; nitrogen-containing heterocyclic compounds such as 4,4'-bipyridine; and one or more of triphosphates and porphyrins.

8. The method for preparing MOF-modified lithium manganese iron phosphate according to claim 1, characterized in that, The soluble metal compound is one or more of the following: titanium oxysulfate, zinc nitrate, copper nitrate, ferric chloride, chromium nitrate, aluminum nitrate, cobalt nitrate, nickel nitrate, and magnesium nitrate.

9. The method for preparing MOF-modified lithium manganese iron phosphate according to claim 1, characterized in that, In step S2, the inlet air temperature of the spray drying is 220~250℃, and the outlet air temperature is 90~105℃; the sintering temperature of the first sintering treatment is 600~800℃, and the sintering time is 2~12h.

10. A lithium manganese iron phosphate cathode material, characterized in that, Prepared using the method described in any one of claims 1-9, comprising a lithium manganese iron phosphate core, and an outer layer sequentially coated with a carbon layer, a MOF layer, and another carbon layer.